Effect Compartment Model for the Evaluation of Tolerance to Psychological Highness Following Smoking Marijuana. (8th July 2022) - Singla, Sumeet; Block, Robert
Abstract: The purpose of this study is to evaluate the development of tolerance, using a population modeling approach, in recreational marijuana users after acute pulmonary administration of tetrahydrocannabinol (THC), a primary ingredient in marijuana. A total of 85 subjects in 3 separate studies smoked marijuana cigarettes (dose = 13–49 mg) under controlled conditions. Each study was designed as a randomized, crossover, double‐blind, and placebo‐controlled study. Up to 5 THC plasma samples and corresponding user‐reported psychological highness were pooled for population modeling analyses. Age, sex, user status, and body mass index were evaluated as covariates. Population pharmacokinetic (PK) parameters were estimated in the 2‐compartment PK model. PK parameters were fixed in the effect compartment model to describe the relationship between THC plasma concentration–psychological highness. The distribution rate constant in the effect compartment was estimated to be 0.988 (95%CI 0.964–1.010)/h. The population mean half‐maximal effective concentration (EC50 ) was 23.8 (95%CI 22.7–24.9) ng/mL. Covariate analysis revealed that user status was a significant covariate, and that chronic users appear to need higher plasma concentrations compared with occasional users to achieve a similar degree of highness. The modeling results conclude that chronic users develop tolerance to euphoria, which is the primary central nervous system effect of smoking marijuana.